Efektifitas Layanan Informasi Dalam Pencegahan Bullying di SMK Negeri 1 Panjatan Kabupaten Kulon Progo DI Yogyakarta - Edy Cahya Saputra (Continuous Education: Journal of Science and Research, 2022)
Bullying is a phenomenon of violence that has spread to the world of education. Guidance and counseling efforts are the right efforts that can prevent bullying. Therefore, it is appropriate as a counseling guidance teacher to take preventive action against this. The purpose of this study is to explore in depth data on the effectiveness of information services in preventing bullying with qualitative research methods that seek to describe research findings and find facts with instruments of observation, interviews and documentation studies. The informants in this study were BK SMK Negeri 1 Panjatan teachers, SMK Negeri 1 Panjatan heads, and SMK Negeri 1 Panjatan students. The results of this study can be seen that the implementation of information services at SMK Negeri 1 Panjatan in terms of its implementation is coordinated, systematic, and has been determined through the Service Unit (Satlan) and Service Implementation Plan (RPL), in preventing bullying by counseling guidance teachers not only solely information services provided but also other services such as group guidance as a follow-up service that aims to achieve self-understanding for victims or students who have the potential to become victims of bullying. Information services in preventing bullying at SMK Negeri 1 Panjatan have been effective and have a good impact on students so that it creates a complete understanding of the benefits of solidarity, mutual respect, and the negative impact of bullying for perpetrators and victims. In this case, it is also assisted by the existence of special programs for the missionary corps, mandatory ablution, dhuha prayers and the participation or coordination of teachers in the field of study, homeroom teachers and counseling guidance personnel in supervising students at SMK Negeri 1 Panjatan.